An alternative explanation for global trends in thermal tolerance. (1st December 2016) - Payne, Nicholas L.; Smith, James A.
Abstract: Ectotherms from higher latitudes can generally perform over broader temperature ranges than tropical ectotherms. This pattern is thought to reflect trends in temperature variability: tropical ectotherms evolve to be 'thermal specialists' because their environment is thermally stable. However, the tropics are also hotter, and most physiological rates increase exponentially with temperature. Using a dataset spanning diverse ectotherms, we show that the temperature ranges ectotherms tolerate (the difference between lower and upper critical temperatures, and between optimum and upper critical temperatures) generally represents the same range of equivalent biological rates (e.g. metabolism) for cool‐ and warm‐adapted species, and independent of latitude or elevation. This suggests that geographical trends in temperature variability may not be the ultimate mechanism underlying latitudinal and elevational trends in thermal tolerance. Rather, we propose that tropical ectotherms can perform over a narrower range of temperatures than species from higher latitudes because the tropics are hotter.